Antimicrobial and photophysical properties of chemically grafted ultra-high-molecular-weight polyethylene - Benkocká, Monika; Lupínková, Simona; Knapová, Tereza; Kolářová, Kateřina; Matoušek, Jindřich; Slepička, Petr; Švorčík, Václav; Kolská, Zdeňka (Materials science & engineering. C, Materials for biological applications, 2019)
Surface of ultra-high-molecular-weight polyethylene (UHMWPE) was modified by chemical methods. Surface was firstly activated by Piranha solution and then grafted with selected amino-compounds (cysteamine, ethylenediamine or chitosan). The next step was grafting of some borane cluster compounds, highly fluorescent borane hydride cluster anti-B18H22 or its thiolated derivative 4,4'-(HS)2-anti-B18H20. Polymer foils were studied using various methods to characterize surface chemistry (X-ray photoelectron spectroscopy), roughness and morphology (atomic force microscopy, scanning electron microscopy), chemistry and polarity (electrokinetic analysis), wettability (goniometry) and photophysical properties (UV-Vis spectroscopy) before and after modification steps. Subsequently some kinds of antimicrobial tests were performed. Immobilization of anti-B18H22 in small quantities onto UHMWPE surface leads to materials with a luminescence. Samples grafted with borane clusters showed significant inhibition of growth for gram-positive bacteria (S. epidermidis). These approaches can be used for (i) luminophores on the base of polymers nanocomposites development and/or (ii) preparation of materials with antimicrobial effects.
Keywords: Staphylococcus epidermidis; borany; Nanocomposites; Nanostructured surfaces; Wettability; Polyethylenes; Boranes; Chemical grafting; Luminophores; antiinfekční látky; nanokompozity; Anti-Infective Agents; Chemical activation; smáčivost; polyethyleny; Antimicrobial effects